Pentecostalism and the Prosperity Gospel in Rivers State - Ogundu, Ibiene R.; Wori, Ezevunwo O. (British Journal of Education, Learning and Development Psychology, 2021)
The prosperity gospel is a biblical ideology propagated by evangelicals or Pentecostals who equate faith with gains especially, financial success. Also, the Pentecostals view wealth and holiness as intrinsically connected and that the most effective and practical method of actualizing prosperity is by complying with the tenets of the gospel which advocates for unreserved giving, positive confession and unwavering faith. Opposing views of Pentecostal gospel, reveal a controlling gospel propagated for the sole gain of preachers. The study examined the concept of Pentecostalism and the prosperity gospel in Rivers State. Three research questions and three null hypotheses guided the study. The population of study comprised of fourteen (14) major Pentecostal churches and their branches operating in Rivers State. The study randomly selected seven pastors from each of the 14 Pentecostal churches and 298 church members as respondents. 396 copies of questionnaires were usable for the data analysis. A self-administered questionnaire (SAQ)was used on a five-point bipolar scale ranging from strongly agree to strongly disagree. Also, personal interviews were carried out. Data collected was analysed using mean and standard deviation. The null hypotheses was tested using Z-test at P< 0.05 level of significance. The analysis was presented in tables based on the research questions posed. Based on the findings, the study concluded that there is no significant difference on the mean opinions of pastors and church members on the effect of prosperity gospel by Pentecostal churches in Rivers State. The study recommends that Rivers State Pentecostal Religious body (CAN, PFN), should set up policies guiding Pentecostal Churches especially, with regard to tithing, offerings among other contributions especially, at this time of economic hardship. The study also contributed to knowledge.
free